Analisis Konsep Jaringan Kerjasama Perpustakaan Luar Negeri - Juni Yanti; Dinda Salsabilla Mahendra; Mutia Atika; Intan Humaira; Yusniah Yusniah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to find out how the cooperation network of foreign libraries in general is, to find out how the concept of cooperation network for foreign libraries is, and to find out what aspects of the constraints that occur in the process of networking cooperation for foreign libraries. The type of research used in this research is library research or library research, namely research conducted through collecting data or scientific writings that aim at research objects or data collection that is library in nature, or studies that are carried out to solve a problem that basically focuses on on a critical and in-depth review of relevant library materials. This research resulted that the collaboration and library network between foreign libraries that have been carried out so far have placed more emphasis on culture where this is due to the existence of cultural similarities (cognate) so that the collaboration that has been carried out is more focused on identifying and maintaining sources of information on Bornean culture. Keywords: Cooperation, Information, Overseas Libraries